Protoplast isolation of Boesenbergia Rotunda cell suspension culture / Tan Hao Cheak - Tan, Hao Cheak (2014)
Establishment of protoplasts system provides a useful platform for cloning and genetic manipulation of ginger plants. In this study, an efficient protocol for developing protoplast isolation and culture for Boesenbergia rotunda has been established. B. rotunda embryogenic cell suspension cultures showed good growth rate (μ = 0.1125) when cultured in plant growth regulator (PGR)-free liquid Murashige and Skoog (MS) basal medium supplemented with 3 % sucrose, where no promotive effect were observed in the presence of any concentrations of 2,4-dichlorophenoxyacetic acid (2,4-D) and sonication treatment. This suspension culture was subsequently used as a source to isolate protoplast using enzyme cocktails. A total number of 1 - 5 × 105 per mL protoplasts were isolated using 0.25 % macerozyme and 1 % cellulase incubated for 24 h under continuous shaking condition of 50 rpm in dark condition. Of the isolated protoplasts, 54.93 % were viable according to fluorescein diacetate staining test. About 7.61 ± 1.65 % cultured protoplasts successfully formed micro-colonies when cultured in liquid MS basal medium supplemented with 9 g/L mannitol, 2 mg/L 1-naphthaleacetic acid (NAA), 0.5 mg/L benzylaminopurine (BAP) and incubated at 25 ± 2 °C in dark condition for 4 weeks. The osmoticum of the culture media were reduced weekly during the protoplast culture period from 9 to 5 % followed by 1 %. These colonies were subsequently transferred to solid MS medium supplemented with 0.5 mg/L BAP for callus initiation. The callus was formed after 5 weeks of culture.